Pengaruh Media Video Scribe Berbasis Model Pembelajaran Group Investigation Terhadap Peningkatan Hasil Belajar di Sekolah Dasar - Ika Dwi Lestari; Jaka Nugraha; Reza Maulana (Upgrade : Jurnal Pendidikan Teknologi Informasi, 2026)
Critical thinking is one of the essential competencies that should be fostered in 21st-century education. However, its implementation at the elementary school level has not yet achieved optimal outcomes, partly because teacher-centered learning approaches remain widely practiced. Therefore, this study aimed to investigate the effect of integrating VideoScribe media with the Group Investigation learning model on the development of fifth-grade elementary students’ critical thinking skills.This study employed a quantitative quasi-experimental design with a non-equivalent control group. The sample consisted of 54 students divided into two groups: 27 students in the experimental class and 27 students in the control class. Data were collected through pretests and posttests and analyzed using the Wilcoxon and Mann–Whitney nonparametric tests. In addition, N-Gain analysis was conducted to measure students’ improvement levels. The findings revealed that the experimental group showed a slight significant improvement in critical thinking skills. The results indicate that integrating VideoScribe media with the Group Investigation model promotes more interactive and collaborative learning, thereby effectively supporting the development of critical thinking skills in elementary school students.